Unveiling the Teaching Methods Adopted in DevOps Courses - Ferino, Samuel; Kulesza, Uirá (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
DevOps practices emerged as an approach focused on coordinating development and operation teams and ensuring rapid and reliable new software releases. Despite the significant demand for preparing new professionals in these practices, there is a reduced number of studies investigating teaching methods in DevOps Education. We investigate the teaching methods reported in the literature. We also performed an analysis based on interviews to identify teaching methods. For both cases, we analyzed their relationship with DevOps educational challenges. Our findings suggest that educators should favor practical methods (e.g., project-based learning) in a collaborative learning environment to teach DevOps.